On Some Psychological Problems of Roma – War Refugees - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2006)
This is a common sense knowledge that Rroma people as ethnical group are socially handicapped, ''hopeless'' and discriminated. Life in Rroma enclaves (ghettos) generated their feeling of adaptableness, isolation and ''different life''. High level of illiteracy and high level ov unemployment generated a famous ''vicious circle of povery''. Like a majority of power class at the bottom of social and ethical hierarchy, they are ''politically invisible''. Wars in ex-Yugoslavia, especially the war for Kosovo and NATO bombing in the last decade of past century, enlarged already existing problems of Rroma people and induced some new which affected Romma – war refuges. As one of the most powerful stresses, war dramatically jeopardizes mental health of the population. Psychological disorders provoked by war vary from anxious and panic attacks to severe post-traumatic stress disorders and reactive psychoses.